Two new species of Bahita Oman, 1938 from Central-Western Brazil (Insecta: Hemiptera: Cicadellidae: Deltocephalinae) - Camisão, Beatriz M.; Takiya, Daniela M. (Zootaxa, 2017)
Two new species of Bahita are described from Goiás State, Brazil: B. sakakibarai sp. nov. and Bahita zanolae sp. nov., which represent the first records of the genus from this state. A key to males of the eleven species of Bahita recorded from Central-Western Brazil is given, and the taxonomic history of the genus is revised.